Maternal Attachment Style, Interpersonal Trauma History, and Childbirth-Related Post-traumatic Stress - MacKinnon, Anna L.; Houazene, Sarah; Robins, Stephanie; Feeley, Nancy; Zelkowitz, Phyllis (Frontiers in Psychology, 2018)
Childbirth-related posttraumatic stress has potentially negative and enduring consequences for the well-being of women and their families. Although research to date has identified attachment style and trauma history as individual risk factors, they have yet to be examined as integrative processes in the development and maintenance of childbirth-related posttraumatic stress. The current investigation aimed to examine whether attachment style may moderate the impact of a history of interpersonal trauma on initial levels and the rate of change in posttraumatic stress symptomatology across the first 6 months of the postpartum period. A large community sample of women were recruited from two Canadian urban hospitals. Childbirth-related posttraumatic stress symptoms were assessed longitudinally at 5 weeks, 2 months and 6 months postpartum. Latent growth curve modeling (n = 251) revealed that attachment style moderated the impact of a history of interpersonal trauma on initial levels and the rate of change in posttraumatic stress symptomatology, while controlling for other well-established psychosocial (e.g., trait anxiety, previous psychopathology, lack of perceived support) and childbirth-related (e.g., mode of birth, labor pain, subjective experience) risk factors. More secure attachment conferred resiliency and more fearful attachment conferred vulnerability among women without a history of interpersonal trauma, while more preoccupied and more dismissing attachment conferred resiliency among women with a history of interpersonal trauma. These findings highlight the importance of understanding the integrative processes among risk and protective factors underlying the development of and ability to cope with childbirth-related posttraumatic stress. Attachment style and trauma history, which can be quickly measured, should be considered as targets in antenatal screening.